Student’s Perspectives on the Efficacy of Tandem Application in Enhancing Speaking Proficiency - Batubara, Putri Fadillah; Maslathif Dwi Purnomo (Institut Agama Islam Negeri Palopo, 2025)
This study aims to explore students' perceptions of the effectiveness of the Tandem application in improving English speaking skills. The background of this research is based on the importance of speaking skills in foreign language learning and the common challenges faced by students, such as awkwardness, anxiety, and limited interaction with native speakers. The research method used is a phenomenological qualitative approach with observation techniques, questionnaires, and in-depth interviews with five students who use the Tandem application. The results showed that the Tandem application helped increase self-confidence, speaking fluency, and the ability to understand various accents and cultural contexts. Students felt bolder speaking with native speakers and experienced an increase in faster speaking responses. However, some respondents highlighted the lack of structured feedback from native speakers and suggested integrating the app with formal teacher-led learning. The findings emphasize the need for collaboration between learning technology and conventional approaches for optimal results in speaking skill acquisition.